Evaluation of mean platelet volume, neutrophil/lymphocyte ratio and platelet / lymphocyte ratio relationship with disease severity and metabolic syndrome in patients with psoriasis vulgaris - Semra Hancer, Hilal; Tugba Alatas, Emine (Annals of Medical Research, 2021)
Aim: Psoriasis is one of the diseases caused by chronic inflammation. It is associated with a number of comorbidities (metabolic syndrome, cardiovascular disease, obesity, non-alcholic fatty liver...). Recently, mean platelet volume (MPV), neutrophil lymphocyte ratio (NLR) and platelet lymphocyte ratio (PLR) were found to be related to systemic inflammation. At the end of this study, the risk of metabolic syndrome in psoriasis will be evaluated and the effect of MPV, NLR, PLR levels will be determined on predicting metabolic comorbidities in psoriasis patients.Material and Methods: This research was planned prospectively. The study consisted of 40 patients with psoriasis vulgaris and 40 healty control group which was similar in age and gender . Patients' informations were recorded and blood pressure, height, weight values were measured. Hemogram parameters, biochemistry values were determined.Results: The count of neutrophiles was higher in the psoriasis; but disease severity and neutrophil count were not related each other. According to our study, MPV values, high density lipoprotein (HDL), fasting blood glucose and body mass index (BMI) were meaningful findings in estimating the development of metabolic syndrome. Conclusion: The use of neutrophil activation markers in addition to neutrophil count in patients with psoriasis may be useful in determining disease severity and activation. In the follow-up of patients with psoriasis, fasting glucose, HDL, BMI value and MPV can help predicting possibility of metabolic syndrome and cardiovascular diseases that may develop in these patients.
Keywords: Metabolic syndrome; neutrophil; platelet; psoriasis